Factors associated with risk of dental caries in primary teeth among pre-schoolers in Seremban, Malaysia - Lee, Zhi Ling (2019)
Dental caries in primary teeth is a serious public health issue among children and it is the most common chronic disease worldwide. Dental caries in primary teeth brings detrimental impacts on child growth and development, as well as their quality of life. As there are limited studies determining risk factors of dental caries in primary teeth among pre-schoolers in Malaysia, this cross-sectional study aimed to determine the associations between parental factors and child factors with dental caries in primary teeth among pre-schoolers in Tabika Perpaduan in Seremban, Negeri Sembilan, Malaysia. A total of 396 pre-schoolers (boys: 49.5%; girls: 50.5%) with a mean age of 5.50±0.62 years, from 26 randomly selected Tabika Perpaduan in Seremban participated in this study. Dental examination was conducted by a dentist from Hospital Tuanku Ja’afar Seremban to record the amount of decayed and filled primary teeth (dft), salivary pH, and presence of visible plaque. Height and weight of the pre-schoolers were measured by the researchers. Information regarding sociodemographic characteristics, feeding practices, oral health knowledge, attitude and behaviours, second-hand smoke exposure, types of sugary food or drinks, as well as frequency and amount of sugar was gathered through a self-administered questionnaire answered by the mothers. A 3-day food record and food frequency questionnaire were also completed by the mothers. Results showed that nearly two-third of the pre-schoolers (64.4%) had dental caries in primary teeth, in which higher proportion of boys (69.4%) experienced dental caries than girls (59.5%; ꭓ2=4.221, p=0.040). On average, each preschooler in this study had nearly four decayed or filled primary teeth (mean±SD dft score=3.66±4.61). Half of the pre-schoolers (52.0%) had visible plaque on their primary teeth. In term of nutritional status, 14.8% of the pre-schoolers were overweight and obese, while 11.8%, 6.9%, and 7.4% were underweight, stunted, and wasted/thin, respectively. The mean energy intake of the pre-schoolers was 1382±293 kcal, with 37.1% of them did not achieve recommended daily energy intake. One in ten of the pre-schoolers (10.6%) was exposed to sugar for more than six times daily. Bread and bun (63.4%) were the most frequently consumed food, followed by biscuits (62.8%), fruits cordial (50.8%), and flavoured snack (50.4%). Half of the pre-schoolers (51.4%) were living in a household which at least one cigarette was smoked inside the house. Multiple logistic regression results showed that pre-schoolers with visible plaque on their teeth (AOR=5.64, 95% CI=2.02-10.56), who were Malay (AOR=4.18, 95% CI=1.16-15.06) or Chinese (AOR=7.59, 95% CI=1.57-36.09), who were from household with at least one cigarette smoked inside the house (AOR=2.43, 95% CI=1.15-5.11), total sugar exposure for more than six times daily (AOR=6.40, 95% CI=1.86-22.02), who did not achieve daily recommended energy intake (AOR=2.82, 95% CI=1.50-5.32), daily intake of fruits flavoured drinks or cordial (AOR=4.11, 95% CI=1.50-11.27), and non-daily intake of honey (AOR=3.99, 95% CI=1.13-14.10) had higher risk of developing dental caries in primary teeth. However, the finding on the association of honey and dental caries should be interpreted cautiously because only 4.9% of the pre-schoolers consumed honey daily in this study, which may lead to lower chance of dental caries among this group of pre-schoolers. More in vitro and in vivo studies are needed to determine the exact mechanism and the potential application of honey in the prevention of dental caries. In conclusion, a high prevalence of dental caries in primary teeth was found in this study. Promoting good oral hygiene, reducing exposure to second-hand smoke, and practicing healthy eating behaviours may help to reduce risk of dental caries among pre-schoolers. Nutritionists should provide specific dietary guidance for parents of young children, particularly regarding sugary food consumption in order to prevent dental caries in pre-schoolers.